2020
DOI: 10.3390/ijms21239051
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Influences the Reproductive Axis and Circulating Levels of microRNAs in Senegalese Sole

Abstract: Kisspeptin regulates puberty and reproduction onset, acting upstream of the brain–pituitary–gonad (HPG) axis. This study aimed to test a kisspeptin-based hormonal therapy on cultured Senegalese sole (G1) breeders, known to have reproductive dysfunctions. A single intramuscular injection of KISS2-10 decapeptide (250 µg/kg) was tested in females and males during the reproductive season, and gonad maturation, sperm motility, plasma levels of gonadotropins (Fsh and Lh) and sex steroids (11-ketotestosterone, testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 91 publications
(120 reference statements)
0
11
0
3
Order By: Relevance
“…Recently, it has been widely accepted that miRNAs were involved in the regulation of P4 synthesis in GCs [ 38 ]. A recent study showed that kp-10 stimulated Senegalese soles’ gonadotropin and testosterone synthesis and induced changes in its plasma miRNAs [ 39 ]. Similarly, we found that kp-10 decreased miR-1246 expression in BGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been widely accepted that miRNAs were involved in the regulation of P4 synthesis in GCs [ 38 ]. A recent study showed that kp-10 stimulated Senegalese soles’ gonadotropin and testosterone synthesis and induced changes in its plasma miRNAs [ 39 ]. Similarly, we found that kp-10 decreased miR-1246 expression in BGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group also showed that kisspeptin could promote the secretion of steroid hormones and cell proliferation in ovarian granulosa cells of Tan sheep in vitro (unpublished data), but the specific molecular mechanism remains unclear. Recent studies have indicated that kisspeptin-10 could significantly change the expression of circulating miRNAs (let-7e, miR-100-5p, and others) obtained from the plasma of gonads of Senegalese Sole, affecting their reproduction [ 26 ]. Kisspeptin-10 has been reported to induce progesterone synthesis in bovine granulosa cells by regulating the expression of miR-146-targeted StAR genes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Kiss2 is more effective than Kiss1 in triggering gonadotropin secretion in this species ( 46 ). Similarly, intramuscular injection of Kiss2 stimulates secretion of Fsh and Lh in Senegalese sole of both sexes ( 94 ). Moreover, a differential and gonadal stage-dependent roles of kisspeptin on Lh release was observed in hybrid bass: Kiss1 increases plasma LH levels during gonadal recrudescence in vivo , whereas Kiss2 stimulates the release of LH during at pre-puberty and gonadal recrudescence ( 17 ).…”
Section: Kisspeptins´ Actions On the Pituitarymentioning
confidence: 99%
“…Similarly, plasma levels of 11-KT in males and E 2 in females are significantly increased in immature Nile tilapia treated with Kiss2, and Kiss2 apparently accelerates the process of spermatogenesis ( 92 ). Recently, Kiss2 was shown to stimulate T secretion in both sexes of Senegalese sole ( 94 ). All these data suggest an effect on the gonads, probably mediated by gonadotropins, but a direct effect of kisspeptins on the gonads have been less considered.…”
Section: Kisspeptins´ Actions On the Gonadsmentioning
confidence: 99%